Investigation of primary mathematics student teachers' concept images: cylinder and cone - (:unkn) unknown (Taylor and Francis Ltd., 2014)
The aim of the present study is to determine the influence of concept definitions of cylinder and cone on primary mathematics student teachers' construction of relevant concept images. The study had a relational survey design and the participants were 238 primary mathematics student teachers. Statistical analyses implied the following: mathematics student teachers did not have sufficient level of knowledge about the concepts of cylinder and cone; concept definitions were insufficient in constructing concept images; providing student teachers with formal definitions of the concepts increased performance in choosing the right models of cylinder and cone from a given set of models but decreased performance in constructing a new cylinder; formal definitions did not affect the selection of models which were not cylinder and cone and the construction of a new cone model. © 2013 Taylor & Francis.
Keywords: concept definition; concept image; cone; cylinder; mathematics student teachers